Mum, why did you did it? (Journal of Parents and Teachers, 2013)
The loss is an inevitable experience for the human being. People establish emotional connections along their lives and when these connections break, they suffer pain for the loss and, therefore, they will experiment the process of grief.  When we talk about the process of grief and the pain that the human being suffers, it is only natural to realize that every person deals with a particular process of grief and it is different from the one that experiment any other person.  This is the reason why we ask ourselves the following question. What is the factor that leaves some people dealing with a complicate process of grief while others do not? In this article, we will try to focus our attention on this question from the analysis of the particular case of Sandra, a 37 years old woman who comes to psychotherapy thirty years after the suicide of her mother. This case will allow us to think about the impact that a sudden and violent loss has on those whom are still alive and suffer it, especially when this happens during the childhood.
Keywords: Psychoterapy; Suicide; Childhood; Family and guidance; education.